Examining Sharia Financial Literacy And Capital Access For MSME Sustainability: A Mixed-Methods Study In East Kalimantan - Priyandono, Lukman; Boubekri, Achref; Kharista, Malinda (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research investigates the relationship between Sharia financial literacy, access to Islamic financing, and the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in East Kalimantan, Indonesia—a strategically important region experiencing accelerated development as the site of the country’s new capital. Adopting a mixed-methods design, the study integrates quantitative data from a survey of 300 MSMEs analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with qualitative evidence obtained through in-depth interviews with MSME actors, Islamic bankers, and regulators. The quantitative results indicate that the constructs of Access to Capital and MSME Resilience exhibit strong reliability and validity, while the Financial Literacy construct requires further refinement, highlighting that general financial knowledge does not necessarily translate into competence in Sharia-compliant financial products. Qualitative findings further identify a communication gap between MSME owners’ demand for accessible and practical financial guidance and the complexity of offerings provided by financial institutions. The study concludes that strengthening MSME sustainability necessitates policy interventions that address these gaps through targeted Sharia financial education and inclusive Islamic financing schemes. This research contributes a validated holistic framework and provides practical policy recommendations for the development of contextualized Islamic financial literacy programs and digital inclusion strategies to reinforce Indonesia’s Sharia-based MSME ecosystem.